2011
DOI: 10.1007/s00190-011-0459-x
|View full text |Cite
|
Sign up to set email alerts
|

VLBI-derived troposphere parameters during CONT08

Abstract: Time-series of zenith wet and total troposphere delays as well as north and east gradients are compared, and zenith total delays (ZT D) are combined on the level of parameter estimates. Input data sets are provided by ten Analysis Centers (ACs) of the International VLBI Service for Geodesy and Astrometry (IVS) for the CONT08 campaign (2008 August 12-26). The inconsistent usage of meteorological data and models, such as mapping functions, causes systematics among the ACs, and differing parameterizations and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…These estimations correspond very well (better than 1 cm) and are consistent with meteorological models (at the centimeter level). Numerous authors have dealt with this subject: Heinkelmann et al (2011), Behrend et al (2002), Niell et al (2001), etc. Among them, Steigenberger et al (2007) and Teke et al (2013) studied ZTD estimations during CONT02 and during all the CONT campaigns, respectively, on the basis of the data of GNSS, VLBI, DORIS, water vapor radiometers, and meteorological models.…”
mentioning
confidence: 99%
“…These estimations correspond very well (better than 1 cm) and are consistent with meteorological models (at the centimeter level). Numerous authors have dealt with this subject: Heinkelmann et al (2011), Behrend et al (2002), Niell et al (2001), etc. Among them, Steigenberger et al (2007) and Teke et al (2013) studied ZTD estimations during CONT02 and during all the CONT campaigns, respectively, on the basis of the data of GNSS, VLBI, DORIS, water vapor radiometers, and meteorological models.…”
mentioning
confidence: 99%
“…The formal error is however in general always underestimating the real uncertainty. Heinkelmann et al (2011) addressed this question by comparing the ZWD results from ten different analysis centres and concluded that overall there was an underestimation with approximately a factor of 2. Their results also show that the formal uncertainties of the ZWD from the different centres for the same experiment also vary with a factor of 2, depending on the assumptions made when setting up the analysis.…”
Section: Intermediate Discussionmentioning
confidence: 99%
“…The ICRF is a catalogue of positions of extragalactic radio sources with the highest precision, which are crucial to many applications. For example, the ICRF provides sources that are observed in the geodetic VLBI observations conducted by the IVS to measure the orientation of Earth in space and station motions (Hellmers et al 2021), which in turn contributes to the realization of the ITRF and allows studies of the motion of the tectonic plates and the interior of the Earth (Carter and Robertson 1993), and measurements of the ionosphere and troposphere which allows for atmospheric studies (Heinkelmann et al 2011). High-accuracy celestial reference frames are also crucial for many other applications such as satellite tracking, orbit determination, and deep-space navigation (Thornton and Border 2000), alignment of the planetary ephemerides (Park et al 2021), studies of special and general relativity (Fomalont et al 2009) such as Galacto-centric acceleration (MacMillan et al 2019), and for phase-referencing observations in astronomy (Beasley and Conway 1995;Rioja and Dodson 2020).…”
Section: Introductionmentioning
confidence: 99%